2014
DOI: 10.21608/jssae.2014.49802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Intervals and Different Plant Densities on Faba Bean Yield, Some Water Relations and Some Soil Properties Under Drip Irrigation System in North Middle Nile Delta Region.

Abstract: Two field experiments were conducted at Sakha Agricultural Research Station, Kafr El-Sheikh Governorate. The site is located at 31 0 07ˉ N Latitude and 30 0 57ˉ E longitude with an elevation of about 6 meters above mean sea level. This location represents the conditions of the North Middle Nile Delta region during the two successive winter growing seasons 2012/2013 and 2013/2014 to investigate the effect of irrigation intervals and plant densities on faba bean yield, some yield attributes and some water relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
6
1
0
Order By: Relevance
“…Increasing the overall mean values for consumptive use efficiency under the conditions of irrigation treatment I 1 (Traditional irrigation ) may be due to increasing the amount of water consumptive use in comparison with other irrigation treatments I 2 ,I 3 and I 4 which exposed to water stress during the growing season . These results are in the same line with those reported by ( Younis, et al,2009) , (Mikhael, et al, 2010) and (Moursi, et al,2014) .…”
Section: -Irrigation Water Efficienciessupporting
confidence: 94%
See 2 more Smart Citations
“…Increasing the overall mean values for consumptive use efficiency under the conditions of irrigation treatment I 1 (Traditional irrigation ) may be due to increasing the amount of water consumptive use in comparison with other irrigation treatments I 2 ,I 3 and I 4 which exposed to water stress during the growing season . These results are in the same line with those reported by ( Younis, et al,2009) , (Mikhael, et al, 2010) and (Moursi, et al,2014) .…”
Section: -Irrigation Water Efficienciessupporting
confidence: 94%
“…Concerning ,water productivity (WP) and productivity of irrigation water (PIW) .The overall mean values for the abovementioned two studied parameters were highly affected by irrigation treatments (amount of irrigation water applied ) as clearly shown in Table (6 3 ,respectively .This means that ,under water stress condition the values of WP and PIW were increased in comparison with nonstressed conditions (Tradition irrigation ,like practice by local farmers in the studied area ) which recorded the lowest values .Increasing the overall mean values for WP and PIW under water stress condition in comparison with nonstressed ones may be attributed to decreasing amount of water consumptive use and irrigation water applied under stressed treatments .These results are in a great harmony with those reported by ( Ibrahim and Abd El-samad, 2009) on "Manfalouty " pomegranate .They indicated that a gradual decrease in water use efficiency (water productivity ) values due to increase the a mount of water applied and consumptive use .Also ,these results are in a great agreement with those obtained by (Mikhael, et al, 2010) on peach trees "Dessert Red" who reported that ,the highest significant values for field water use efficiency (productivity of irrigation water ) were recorded under irrigation trees at 70% of field capacity ( moderate irrigation regime ) in both seasons followed in descending order by those irrigated at 60% and 80% of field capacity . The same finding were found by (El-Abd ,et al, 2012) on "Navel orange trees " and (Garcio and Brunton, et al, 2013) on peach trees and (Moursi, et al, 2014) on Faba bean…”
Section: -Irrigation Water Efficienciessupporting
confidence: 81%
See 1 more Smart Citation
“…Increasing the overall mean values for WP and PIW under the conditions of irrigation treatments (I 3 ) in comparison with other irrigation treatments I 2 and I 1 could be attributed to decreasing amount of both water applied and consumptive use. These results are identically with those reported by (Shabana, 2010) and (Moursi et al, 2014). Regarding the impact of foliar application, the highest overall mean values TABLE 6.…”
Section: Water Consumptive Use (Cu) M 3 /Fed and Consumptive Use Effisupporting
confidence: 90%
“…Such trend is mainly due to the differences in climatic conditions and sowing date between both seasons of study. Similar conclusion was reached by Mohammad (2014), Moursi et al (2014) and Jabow et al (2015). Appropriate frequency of irrigation can be determined from the available soil moisture retaining capacity and the rate of faba bean evapotranspiration taking into consideration that it better replenish the soil moisture when about 50% of the total available soil water is exhausted (Allen et al,1998) With respect to, the effect of applied different concentrations (0.2, 0.1, 0.05 and zero %) of polyvinyl alcohol as soil conditioner on total mean actual faba bean evapotranspiration (ETa) results illustrated in Table 3& Table 4 and Figure1.…”
Section: Water Relations Of Faba Bean Crop: Faba Bean Actual Evaopotranspiration (Eta) Affected By Different Water Regimes and Poly Vinylsupporting
confidence: 88%